Peningkatan Kreativitas Siswa Bidang Teknologi dan Otomasi melalui Pelatihan Arduino - Junaidi Akbar; Amin Suyitno; Abidin Abidin; Dwi Mahadiyan Widya H (Pusat Riset dan Inovasi Nasional, 2024)
Increasing student creativity the field technology and automation is very important in facing rapid development of technology. Training using Arduino as a tool learning that can be used as one of the effective methods increase student creativity. This training aims assess the impact Arduino training increasing student creativity the field of technology and automation. The community service team provides training on data communication systems utilizing Bluetooth HC-05 connection control an LED output via cellphone. The method used is providing a teaching module that is disassembled, direct practice on hardware and software by following the instruction manual using the teaching module. The results of training questionnaire instrument given participants in terms of understanding material instructions with C Compiler program 63.82% very satisfied, 25.53% satisfied and 10.63% quite satisfied. In terms of training facilities 80.85% very satisfied, 14.89% satisfied and 4.25% quite satisfied. In terms of increasing competence the world of automation 85.1% very satisfied, 2.12% satisfied and 12.76% quite satisfied. In terms of professional exposure or presentation material and media 74.46% very satisfied, 17.02% satisfied and 8.51% quite satisfied which was attended by 47 participants. This training shows the enthusiasm participants in recognizing technology and automation